Towards integrated management of Australia's ecologically significant military training areas. Issue 2 (3rd April 2018) - Zentelis, Rick; Lindenmayer, David; Roberts, J Dale; Dovers, Stephen
ABSTRACT: Military training areas (MTAs) in Australia are estimated to cover 2.3 per cent of the continent, or 18M hectares. Current Australian Defence Department policy requires that the values of MTAs be maintained by integrated land management (ILM), which can be defined as the assessment and balancing of competing demands to achieve optimal management of an area. We completed two evaluations of the Australian MTA management framework to determine whether it contained the key features of ILM. Phase 1 of this work involved a desktop study of whether: (1) there are clear management objectives for Australian MTAs that enable adaptive management; (2) the management framework is hierarchical allowing for management cohesion and integration; (3) elements of the hierarchy are consistent and have common objectives; and (4) there was dedicated funding. Phase 2 consisted of meetings with key Australian Department of Defence officials to discuss the operation of the MTA management framework. Our evaluation suggests that the Australian MTA management framework lacks key elements of ILM. Two major failings are a lack of clear, measurable management objectives negating the ability to implement adaptive management, and lack of a clear hierarchy of documentation, making coherent management impossible.